2017
DOI: 10.1186/s11689-017-9195-8
|View full text |Cite|
|
Sign up to set email alerts
|

Delta rhythmicity is a reliable EEG biomarker in Angelman syndrome: a parallel mouse and human analysis

Abstract: BackgroundClinicians have qualitatively described rhythmic delta activity as a prominent EEG abnormality in individuals with Angelman syndrome, but this phenotype has yet to be rigorously quantified in the clinical population or validated in a preclinical model. Here, we sought to quantitatively measure delta rhythmicity and evaluate its fidelity as a biomarker.MethodsWe quantified delta oscillations in mouse and human using parallel spectral analysis methods and measured regional, state-specific, and developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
146
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(175 citation statements)
references
References 64 publications
28
146
1
Order By: Relevance
“…The seizure phenotype is reported to be more prominent in AS patients with a maternal deletion of chromosomal 15q11-q13 region, presumably due to the haploinsufficiency of a cluster of GABA receptors including GABRB3 in the distal end (Dan 2009; DeLorey et al 1998; Egawa et al 2008). The electroencephalogram (EEG) in AS patients has a characteristic pattern of large-amplitude slow-spike waves at 1–2 or 4–6 Hz (Sidorov et al 2017; Vendrame et al 2012). A significant fraction of clinical seizures is medically intractable and the quality of life is significantly compromised in these individuals (Tan and Bird 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The seizure phenotype is reported to be more prominent in AS patients with a maternal deletion of chromosomal 15q11-q13 region, presumably due to the haploinsufficiency of a cluster of GABA receptors including GABRB3 in the distal end (Dan 2009; DeLorey et al 1998; Egawa et al 2008). The electroencephalogram (EEG) in AS patients has a characteristic pattern of large-amplitude slow-spike waves at 1–2 or 4–6 Hz (Sidorov et al 2017; Vendrame et al 2012). A significant fraction of clinical seizures is medically intractable and the quality of life is significantly compromised in these individuals (Tan and Bird 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In apparent contradiction to the above arguments and data, children with Angelman syndrome (AS) display the rich spectrum of purposeful behavior that implies conscious awareness (as seen here) [33][34][35] while exhibiting the chanting EEG phenotype typical of states of reduced consciousness ( Fig. 1) [36][37][38][39] . Although the AS EEG phenotype has long been described in clinical reports 40 , we are the first to characterize the degree to which the awake EEG in children with AS can support complex dynamics and, moreover, that these dynamics are demonstrably lowered as consciousness decreases during sleep.…”
Section: Introductionmentioning
confidence: 56%
“…) that were also observed in animal models of AS (Sidorov et al . ). However, the connection between these EEG characteristics and behavioural or cognitive features of AS is currently unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Measures of electrical brain activity may offer another way to assess social information processing in AS. To date, electroencephalography (EEG) studies in AS noted distinct patterns of delta-band activity (Vendrame et al 2012) that were also observed in animal models of AS (Sidorov et al 2017). However, the connection between these EEG characteristics and behavioural or cognitive features of AS is currently unknown.…”
Section: Introductionmentioning
confidence: 99%